Prospecting for cytotoxic and antiprotozoal 4‐aryl‐4H‐chromenes and 10‐aryldihydropyrano[2, 3‐f]chromenes. Issue 10 (23rd August 2018) - Martin, Erlon F.; Mbaveng, Armelle T.; de Moraes, Milene H.; Kuete, Victor; Biavatti, Maique W.; Steindel, Mario; Efferth, Thomas; Sandjo, Louis P.
Abstract: Different studies reported that genetic predisposition or metabolic dysfunction are the risk factors for cancer. Infectious parasitic diseases were listed among factors that predispose to cancer. Because of the resemblance between the life cycle of cancer cells and some parasites, this study aimed to prepare pyran derivatives with cytotoxic and antiprotozoal potencies. Therefore, 7 chromenes, 10 pyranocoumarins, and an unexpected intermediate were obtained from a multi‐reagent one‐pot reaction. These compounds were evaluated for their cytotoxicity on sensitive and resistant leukemia cancer cells lines and against two protozoan parasites, namely Trypanosoma cruzi and Leishmania amazonensis amastigote. Promising cytotoxicity (IC50 values of less than 1 µM) was obtained for two of the synthetic products (12 and15 ). Compound12 induced apoptosis and cell cycle arrest in CCRF‐CEM leukemia cells in G0/G1 while compound15 and doxorubicin induced apoptosis and arrest in the S and G2/M phases. Ten of these products showed trypanocidal activity, while only five of them were weakly active on L. amazonensis . Three of the obtained pyrans showed significant cytotoxicity and antitrypanocidal activity, simultaneously. Nevertheless, all antiparasitic compounds revealed potency with low selectivity toward THP‐1 cells used as host. Abstract : Seventeen chromenes and an unexpected compound from the Knoevenagel condensation were prepared and assayed against drug‐sensitive and resistant leukemic cancer cells lines. The antiparasitic effects against the intracellular forms of Trypanosoma cruzi and Leishmania amazonensis were also evaluated. Compounds10–12 and15 showed promising cytotoxicity against both cancers. Compounds4, 10, and12 were more trypanocidal than benznidazole.